2018
DOI: 10.1007/978-1-4939-7831-1_3
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution FluoRespirometry and OXPHOS Protocols for Human Cells, Permeabilized Fibers from Small Biopsies of Muscle, and Isolated Mitochondria

Abstract: Protocols for High-Resolution FluoRespirometry of intact cells, permeabilized cells, permeabilized muscle fibers, isolated mitochondria, and tissue homogenates offer sensitive diagnostic tests of integrated mitochondrial function using standard cell culture techniques, small needle biopsies of muscle, and mitochondrial preparation methods. Multiple substrate-uncoupler-inhibitor titration (SUIT) protocols for analysis of oxidative phosphorylation (OXPHOS) improve our understanding of mitochondrial respiratory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 49 publications
1
149
0
1
Order By: Relevance
“…This means that it would be a challenge to observe true changes in mitochondrial capacity using the OROBOROS technology, since most studies do not report such large increases following exercise training (−9% to 20%). 18,19,32,[34][35][36][37][38] We acknowledge that some of the studies have observed significant changes in mitochondrial respiration without reaching the effect sizes we presented here. This implies that although such studies were significant, the sample sizes were too low to detect the magnitude of changes they reported at 80% power.…”
Section: F I G U R E 3 Minimum Sample Size Required To Detect Increasmentioning
confidence: 59%
“…This means that it would be a challenge to observe true changes in mitochondrial capacity using the OROBOROS technology, since most studies do not report such large increases following exercise training (−9% to 20%). 18,19,32,[34][35][36][37][38] We acknowledge that some of the studies have observed significant changes in mitochondrial respiration without reaching the effect sizes we presented here. This implies that although such studies were significant, the sample sizes were too low to detect the magnitude of changes they reported at 80% power.…”
Section: F I G U R E 3 Minimum Sample Size Required To Detect Increasmentioning
confidence: 59%
“…A high respiratory capacity is crucial for high malignant and invasive potential 45 . In contrast to tumors, human skeletal muscle and fibroblasts heavily rely on N-pathway capacity 46,47 and a similar compensatory mechanism is not known for mt-myopathies. Ultimately, our results suggest that the immediate net effect of deleterious mtDNA mutations is compensated and does not hamper cellular ATP homeostasis in primary human PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal-specific mitochondrial dysfunction in the young SCA1 mice. In order to investigate whether the brain abnormalities and behavioral deficits identified might be related to mitochondrial dysfunction, we employed high-resolution respirometry to measure mitochondrial respiration in the cerebellar and the hippocampal tissue of the SCA1 mice and their healthy littermates (N = 6 SCA1 and 5 WT mice; aged 11-13) applying the substrate-uncoupler-inhibitor titration (SUIT) protocol 31 (Fig. 7a) and citrate synthase activity measurements (Suppl.…”
Section: Hippocampal Atrophy Precedes Cerebellar Degeneration and Refmentioning
confidence: 99%